Enhanced gravity-driven membrane filtration for purifying roof rainwater using multi-walled carbon nanotubes tuned PVDF hollow fiber membranes - Chen, G.;Li, S.;Li, X.;Li, X.;Liu, B.
The collection and reuse of roof rainwater can alleviate water shortage for daily life. In this study, polyvinylidene fluoride hollow fiber membranes tuned with three multi-walled carbon nanotubes (pure MWCNTs, MWCNTsCOOH, and MWCNTs-OH) were prepared using a non-solvent induced phase separation method for gravitydriven membrane filtration to purify roof rainwater. The results showed that the MWCNTs were distributed on the membrane surface and throughout the porous structure of the cross-section, which changed the pore structure parameters and hydrophilicity. The pure water flux of the MWCNTs tuned membranes increased by 152.5 percent at 1.0 bar, and the rejection rates of humic acid and bovine serum albumin increased from 97.4 percent and 75.7 percent to 98.9 percent and 96.3 percent, respectively. The extended Derjaguin, Landau, Verwey, and Overbeek (xDLVO) theory states that the presence of MWCNTs leads to changes in the physicochemical properties of the membrane surface, resulting in membranes with different anti-fouling behaviors. A gravity-driven membrane filtration test was continuously operated for 100 days, and all membranes removed 25.0-26.7 percent, 49.5-53.0 percent, and 89.0-93.3 percent of total dissolved solids, dissolved organic carbon, and turbidity from roof rainwater, respectively. However, the pure MWCNTs modified membrane with relatively hydrophobic properties showed a 12.4 percent increase in flux over the unmodified membrane. Importantly, the presence of the MWCNTs in the membrane changed the microbial diversity in the biofilter cake layer.
Artículo
Keywords: MWCNTS; PVDF HOLLOW FIBER MEMBRANE; XDLVO THEORY; GRAVITY-DRIVEN MEMBRANE FILTRATION; MICROBIAL DIVERSITY